Auxiliary cementitious material compositions and methods of manufacture

CN119585222APending Publication Date: 2025-03-07ENVICORE INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380057732.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-04
Filing Date
2023-08-04
Publication Date
2025-03-07

Smart Images

  • Figure CN119585222A_ABST
    Figure CN119585222A_ABST
Patent Text Reader

Abstract

A method for preparing an auxiliary cementitious material is provided. The method comprises: contacting a mineral stream with an acid to form an activated mineral stream; reducing the moisture content of the mineral stream; and comminuting the mineral stream to form an auxiliary cementitious material. A method of extracting metals from a mineral stream is provided. The method includes contacting a mineral stream with an acid to form an activated mineral stream; filtering the activated mineral stream to extract a leachate comprising metals; and neutralizing the acid.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority and filing benefit of U.S. Provisional Patent Application No. 63 / 395,285, filed on August 4, 2022, entitled “Supplementary Cementitious Material Compositions and Methods of Making”, and the specification of which is incorporated herein by reference. Technical Field

[0003] The present invention relates to methods of making materials and compositions comprising supplementary cementitious materials. Background Art

[0004] Note that the following discussion may cite one or more publications by one or more authors and the year of publication, and that certain publications are not considered prior art with respect to the present invention because the publication date is recent. Discussion of such publications is given herein for the purpose of making the background more complete and is not to be construed as an admission that such publications are prior art for patentability determination purposes.

[0005] Cement is an essential component of industrialized societies and is the second most consumed product worldwide after drinking water. Cement is a key ingredient in concrete and is used in almost all structures, including houses, skyscrapers, dams, roads and bridges. At the same time, cement is also a major contributor to global CO2 emissions. Cement manufacturing accounts for up to 7% of global CO2 emissions, and every ton of cement produced results in one ton of CO2 released into the atmosphere. Pressure on the cement industry to reduce carbon emissions from society as well as from governments and investors is rapidly increasing. Therefore, achieving net zero emissions by 2050 is a key goal for cement companies around the world.

[0006] Supplementary cementitious materials ("SCMs") are prepared using globally abundant waste mineral streams such as tailings waste from mining operations. Depending on the characteristics of the waste stream, different preparation methods can be used to prepare SCMs. One method involves low temperature chemical activation of the minerals, combined with grinding for further activation and size reduction. Other methods include thermal activation combined with chemical activation and ball milling for size reduction and activation. SCMs can be used in concrete compositions to reduce CO2 emissions associated with cement production.

[0007] SCMs have been used to reduce CO2 emissions associated with Portland cement. As various portions of Portland cement are replaced by SCMs, the environmental impact of concrete is improved, including reductions in greenhouse gases ("GHG") and air pollutants. In addition, reusing SCMs as raw materials for other operations reduces waste, as SCMs are often byproducts of other industrial processes and are often discarded in landfills. The use of cementitious blends not only results in stronger, more durable high-performance concrete, but also helps reduce global climate impact by reducing energy consumption and GHG emissions. Examples of commonly used SCMs include ground granulated blast furnace slag ("GGBFS"), a byproduct of the steel industry; fly ash, a byproduct of coal combustion in power plants; other pozzolans, such as calcined clay; metakaolin; and silica fume. SCMs are also characterized by pozzolanic materials having amorphous siliceous or siliceous and aluminous contents. Amorphous siliceous or siliceous and aluminous contents participate in a pozzolanic reaction with Ca(OH)2 to produce hydrated calcium silicate compounds having cementitious properties. Some SCMs, such as fly ash, have some disadvantages, including slower strength gain; longer setting time; increased need for air entrained mixture; geographical restrictions; and most critically, future availability (due to the closure of coal-fired power plants). The supply of SCM is currently insufficient to meet demand and is declining. The shortage of fly ash in certain markets has also driven the cost of SCM waste to increase. Other SCMs, such as metallurgical slag, volcanic ashes such as natural volcanic ashes and metakaolin, cannot completely replace fly ash due to their low supply volume, geographical restrictions and higher supply prices. Volcanic ashes can also be prepared artificially. For example, calcined clay or metakaolin can be prepared from kaolin minerals. The calcination temperature used to prepare calcined clay is generally lower than that used for cement preparation, and there is no CO2 emission caused by the decomposition of limestone in cement. Therefore, activating minerals with siliceous or siliceous and aluminous contents to prepare SCM can play a major role in carbon reduction in the cement industry.

[0008] Tailings can include solid waste generated from the beneficiation and enrichment processes performed by the mineral mining industry and are available in huge quantities. 3 Tailings waste is expected to increase to 700+ billion m in the next five years 3 The chemical composition of the tailings consists mainly of SiO2, Al2O3, CaO and Fe2O3 and similar compounds. However, these minerals are mostly non-reactive due to their high crystallinity and cannot be classified as volcanic ash.

[0009] Fly ash and slag are the main SCMs currently used for blending in cement mixes. However, the cement industry has driven demand to the point where these waste materials are as expensive as cement in some places. In addition, these main SCMs are subject to geographical restrictions and reduced production in the near future due to the closure of coal-fired power plants. Natural pozzolans are another source of SCMs, but are subject to geographical restrictions. Similarly, calcined clay and metakaolin can be used, but require high temperature calcination (e.g., 700°C-900°C).

[0010] The major problem associated with the global availability of large amounts of SCM can be solved using tailings waste from the mining industry. Tailings not only provide a huge source of sustainable building materials, but their use in SCM also eliminates the environmental impact of both the mining industry and the construction industry. In addition, mineral tailings also have large amounts of residual metals such as nickel, copper, etc.

[0011] Therefore, it is necessary to prepare SCM sustainably to meet the huge demand of cement industry. Large volume of tailings waste can become the outstanding source of SCM preparation. This paper describes a method for preparing SCM from tailings using a combination of acid activation or low temperature calcination at room temperature and acid activation at room temperature. In certain embodiments, for example, in an embodiment for mineral tailings, the feed can be dehydrated to reclaim the energy transition metals, such as nickel and copper, leached from water. Summary of the invention

[0012] Embodiments of the present invention are directed to a method of preparing a supplementary cementitious material, the method comprising: contacting a mineral stream with an acid to form an activated mineral stream; reducing the moisture content of the mineral stream; and comminuting the mineral stream to form a supplementary cementitious material.

[0013] In another embodiment, the mineral stream comprises tailings. In another embodiment, the mineral stream is contacted with the acid for about 1 to about 24 hours. In another embodiment, reducing the moisture content comprises drying. In another embodiment, pulverizing comprises ball milling. In another embodiment, the acid comprises hexafluorosilicic acid. In another embodiment, the acid comprises sulfuric acid. In another embodiment, the acid comprises phosphoric acid. In another embodiment, the method further comprises calcining the activated mineral stream. In another embodiment, the activated mineral stream is calcined at a temperature of about 500° C. to about 700° C. In another embodiment, the mineral stream comprises asbestos tailings. In another embodiment, the mineral stream comprises laterite tailings. In another embodiment, the mineral stream comprises oil sands tailings.

[0014] Embodiments of the present invention also relate to a method of extracting metals from a mineral stream, the method comprising: contacting the mineral stream with an acid to form an activated mineral stream; filtering the activated mineral stream to extract a leachate comprising the metals; and neutralizing the acid.

[0015] In another embodiment, the acid comprises hexafluorosilicic acid. In another embodiment, the mineral stream comprises tailings. In another embodiment, the mineral stream comprises sludge. In another embodiment, the mineral stream comprises slag. In another embodiment, neutralizing the acid comprises contacting the activated tailings with a caustic. In another embodiment, the caustic comprises lime.

[0016] The further scope of applicability of the present invention will be explained in part in the following detailed description in conjunction with the accompanying drawings, and in part will become apparent to those skilled in the art after reviewing the following or can be learned by practicing the present invention. The objects and advantages of the present invention can be realized and obtained by means of the means and combinations particularly pointed out in the appended claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings are incorporated into and constitute a part of the specification, illustrate one or more embodiments of the present invention, and together with the description, serve to explain the principles of the present invention. The accompanying drawings are only for the purpose of illustrating one or more embodiments of the present invention and should not be interpreted as limiting the present invention. In the drawings:

[0018] Figure 1 is a schematic diagram showing the preparation of SCM at room temperature using acid activation of tailings according to an embodiment of the present invention;

[0019] Figure 2 is a schematic diagram showing the preparation of SCM at room temperature using acid activation and calcination of tailings according to an embodiment of the present invention;

[0020] Figure 3 is a graph showing the compressive strength of SCM cement compositions prepared from oil sands tailings after 7 days and 28 days compared to cement according to embodiments of the present invention;

[0021] Figure 4 is a graph showing the compressive strength of SCM cement compositions prepared from zinc tailings compared to cement according to embodiments of the present invention after 7 days and 28 days;

[0022] Figure 5 is a graph showing the compressive strength of SCM cement compositions prepared from copper tailings compared to cement after 7 days and 28 days according to an embodiment of the present invention;

[0023] Figure 6is a graph showing the compressive strength of SCM cement compositions prepared from asbestos tailings compared to cement after 7 days and 28 days according to an embodiment of the present invention;

[0024] Figure 7 is a graph showing the compressive strength of SCM cement compositions prepared from laterite tailings according to an embodiment of the present invention after 7 days and 28 days;

[0025] Figure 8 is a graph showing the compressive strength of SCM cement compositions prepared from recycled concrete according to an embodiment of the present invention after 7 days and 28 days;

[0026] Fig. 9 is a graph showing the compressive strength of an SCM cement composition prepared from nickel tailings after 7 days according to an embodiment of the present invention;

[0027] Fig.10 is a graph showing the compressive strength of an SCM cement composition prepared from nickel tailings after 28 days according to an embodiment of the present invention;

[0028] Fig.11 is a graph showing the compressive strength of an SCM cement composition prepared from copper tailings after 7 days according to an embodiment of the present invention;

[0029] Fig.12 is a graph showing the compressive strength of an SCM cement composition prepared from copper tailings after 28 days according to an embodiment of the present invention;

[0030] Fig.13 is a graph showing the compressive strength of a SCM cement composition prepared from bottom ash, basalt, copper slag and zeolite after 7 days according to an embodiment of the present invention;

[0031] Fig.14 is a graph showing the compressive strength of an SCM cement composition prepared from bottom ash, basalt, copper slag and zeolite according to an embodiment of the present invention after 28 days. DETAILED DESCRIPTION

[0032] The present invention relates to a method for preparing a supplementary cementitious material as a raw material for use in concrete compositions using waste streams and / or mineral tailings.

[0033] The present invention also relates to concrete compositions comprising supplementary cementitious materials derived from waste streams and / or mineral tailings.

[0034] The term "mineral stream" is defined herein to mean any tailings, tailings mineral and / or waste stream.

[0035] The terms "tailings" or "tailings mineral" are used interchangeably and are defined herein as the waste material remaining after a target mineral has been extracted from an ore, tailings, waste, oil and gas operation or other process.

[0036] The term "waste stream" or "waste streams" is defined herein as waste materials left after an industrial, mining or manufacturing process. Waste streams include, but are not limited to, recycled concrete, bottom ash, basalt, copper slag, zeolite or other materials.

[0037] The term "mineral" is defined herein as a solid chemical compound comprising a crystalline structure.

[0038] The term "pozzolan" is defined herein as a siliceous or siliceous and aluminous material which by itself has little gelling value but which will react chemically with calcium hydroxide to form a compound having gelling properties.

[0039] ASTM C618 refers to the standard specification for coal fly ash and raw or calcined natural pozzolans for use in concrete as defined by ASTM International.

[0040] ASTM C311 refers to the Standard Test Methods for Sampling and Testing Fly Ash or Natural Pozzolan for Portland Cement Concrete as defined by ASTM International.

[0041] The term "acid" or "acids" is defined herein as a solution having a pH below 7.

[0042] The term "tank" is defined herein as a vessel, chamber, container, receptacle, and / or other object capable of containing a fluid. The term should encompass vessels, chambers, containers, receptacles, and / or other objects of any suitable size or material. For example, it may include a large acid-resistant tank for mining applications.

[0043] The term "metal" or "metals" is defined herein as a compound, mixture or substance containing metal atoms. The term "metal" or "metals" includes, but is not limited to, metal hydroxides, metal oxides, metal salts, elemental metals, metal ions, non-ionic metals, minerals, or combinations thereof. The metal may include, but is not limited to, neodymium ("Nd"), praseodymium ("Pr"), dysprosium ("Dy"), copper ("Cu"), lithium ("Li"), sodium ("Na"), magnesium ("Mg"), potassium ("K"), calcium ("Ca"), titanium ("Ti"), vanadium ("V"), chromium ("Cr"), manganese ("Mn"), iron ("Fe"), cobalt ("Co"), nickel ("Ni"), cadmium ("Cd"), zinc ("Zn"), aluminum ("Al"), silicon ("Si"), silver ("Ag"), tin ("Sn"), platinum ("Pt"), gold ("Au"), bismuth ("Bi"), lanthanum ("La"), europium ("Eu"), gallium ("Ga"), scandium ("Zn"), and tantalum ("T). The invention may be any of the following: a) stellar metal ("e"), b) stellar metal ("e"), c) stellar metal ("e"), d ...

[0044] The present invention also relates to a method for preparing SCM by tailings activation. Tailings can comprise oxygenates, which include but are not limited to SiO , Al O , CaO and Fe O or their combination. Tailings can comprise high crystallinity, for example about 80%, and can not function as volcanic ash and / or be not classified as volcanic ash. The increase of the specific surface area of ​​volcanic ash and / or the reduction of granularity can expose larger surface to chemical reaction to enhance reactivity. Amorphous volcanic ash and / or SCM structure can be more reactive than crystalline structure, because of the larger mobility of their atoms and the positioning on the surface.

[0045] Tailings and / or waste streams (e.g., mineral streams) can be activated to at least partially change their crystalline structures and form amorphous structures. The activation of tailings minerals and / or waste streams comprises contacting the tailings with acid. Acid can include but is not limited to HCl, HNO , H 2 SO 4 , H 2 [SiF 6 ] and organic acids including but not limited to citric acid and carbonic acid or their combinations. Hexafluorosilicic acid (" HFS ") acid can be used for tailings activation, because of the higher dissolution rate of silicate in the presence of fluoride ions. Acid activation can cause the dissolution of tailings and / or waste streams, accompanied by the loss of their crystalline structures, and form residual amorphous structures. Acid activation can be continued with ball milling to reduce particle size and increase specific surface area. In some cases, ball milling can be completed first to increase specific surface area, followed by acid activation to cause structural disorder and reduce crystallinity. The SCM obtained can be used to replace approximately at least 20% of the cement in the mortar mix subsequently, and can be used for compressive strength measurement after 7 days and 28 days or other suitable time periods.

[0046] Tailings and / or waste streams can be crystalline. Tailings and / or waste streams can be crystalline in structure at least about 10%, about 10% to about 99%, about 20% to about 97%, about 30% to about 95%, about 40% to about 90%, about 50% to about 80%, about 60% to about 70%, or about 99%.

[0047] Another aspect of the present invention includes activating tailings mineral and / or waste stream by calcining. Calcination can occur at a temperature of at least about 400°C, about 400°C to about 650°C, about 450°C to about 600°C, about 500°C to about 550°C, or about 600°C. Calcination can be continued with acid activation and / or ball milling. Tailings mineral and / or waste stream can be first ball milled, which is then followed by calcination to ensure the appropriate calcination of the mineral. Calcination can cause a partial reduction in crystallinity, which can be further reduced by acid activation. The combination of calcination and acid activation can cause amorphization of highly crystalline tailings mineral and / or waste stream. Amorphization can allow tailings to be suitable as SCM. For some tailings and / or waste streams, separate calcination or acid activation may not achieve amorphization of the tailings mineral that is enough to act as an SCM that produces a strength similar to cement at a 20% replacement level. The prepared SCM can then be used to replace at least about 5%, about 5% to about 40%, about 10% to about 35%, about 15% to about 30%, about 20% to about 25%, or about 40% of the cement in the mortar mix. The replacement can be completed in accordance with ASTM C618, and the measurement of compressive strength can be completed after 7 days and 28 days or other suitable time periods.

[0048] Tailings mineral can include but not limited to oil sands tailings, zinc, lead tailings, copper tailings, base metal tailings, precious metal tailings, coal waste tailings, asbestos tailings, nickel laterite tailings, gold tailings, diamond tailings, silver tailings, aluminum tailings, iron tailings, clay tailings or their combination. Waste streams can include but not limited to recycled concrete, glass, fly ash or their combination. Calcination and acid activation can be used with tailings and / or waste streams activated, to replace the cement in the mortar mix for example 5% to 40% percentage.

[0049] Tail stock and / or waste stream can be contacted with acid (for example, ageing) at least about 1 hour, about 1 hour to about 36 hours, about 4 hours to about 32 hours, about 8 hours to about 28 hours, about 12 hours to about 24 hours, about 16 hours to about 20 hours or about 36 hours. Tail stock and / or waste stream can be contacted with acid (for example, ageing) to form slurry. Slurry can be aged and / or slurry can be placed to form sludge. Sludge can be dried to have at least about 0.1%, about 0.1% to about 2%, about 0.3% to about 1.5%, about 0.5% to about 1.0% or about 2% moisture content. The dried sludge can be ground, including but not limited to ball or roller milling or other pulverization, and sieved to form SCM particles having a diameter of at least about 5 μm, about 5 μm to about 50 μm, about 10 μm to about 45 μm, about 15 μm to about 40 μm, about 20 μm to about 35 μm, about 25 μm to about 30 μm, or about 50 μm.

[0050] Go to the attached picture, Figure 1 The schematic diagram of the SCM preparation at room temperature using the acid activation of tailings is shown. For acid activation, dry or moist tailings sludge is mixed with HFS acid. Subsequently, tailings slurry is placed to react 1-24 hour in aging tank, which depends on the composition of tailings, thereby forming sludge (for example, activated tailings). After acid treatment, sludge is fed to dryer (for example, rotary dryer) to reduce moisture content to less than for example 1%, to ensure suitable dry grinding in mill or other pulverizing processes. After grinding of the tailings activated by acid, the SCM obtained is sieved to a certain size limit (generally less than 45 μm) and bagged. Activation process 10 illustrates that acid and tailings mixture 12 are arranged in mixing tank 14 and are allowed to react in aging tank 16 to form the tailings sludge (for example, activated tailings) processed. Activated tailings are dried in dryer 18 and ground in ball mill 20 to prepare SCM product 22.

[0051] Figure 2The schematic diagram of the SCM preparation using the acid activation of tailings and calcination is shown. The tailings of acid activation are further calcined at a temperature of about 500 ℃-700 ℃, so that the tailings are further activated. The tailings feed ball milling and bagging after acid activation and calcination are used for use. Activation process 24 illustrates that acid and tailings mixture 12 are arranged in the mixing tank 14 and are allowed to react in the aging tank 16 to form the tailings sludge (for example, activated tailings) processed. The activated tailings are dried in the dryer 18, heated in the calciner 26, and ground in the ball mill 20 to prepare the SCM product 28.

[0052] Figure 3 The compressive strength of SCM prepared by oil sand tailings after 7 days and 28 days is shown. The compressive strength of mortar samples prepared with 20% of the SCM from oil sand tailings is shown. The SCM from oil sands (" OS ") with polyacrylamide (" PAM "), hexafluorosilicic (" HFS ") acid, benzyltrimethylammonium chloride (" BTMAC "), ball milling (" BM "), and / or calcination (" C ") is compared with cement. The compressive strength of the SCM from oil sand tailings is not obviously different from cement.

[0053] Figure 4 The compressive strength of SCM prepared by zinc tailings after 7 days and 28 days is shown. The compressive strength of mortar samples prepared with 20% of the SCM from zinc tailings is shown. The SCM from zinc tailings ("ZT") with hexafluorosilicic ("HFS") acid, ball milling ("BM"), calcination ("C"), and / or sulfuric acid ("H2SO4") is compared with cement. The compressive strength of the SCM from zinc tailings is not significantly different from cement.

[0054] Figure 5 The compressive strength of SCM prepared by copper tailings after 7 days and 28 days is shown.The compressive strength of mortar samples prepared with 20% of the SCM from copper tailings is shown.SCM from copper tailings (" Cu ") with hexafluorosilicic acid (" HFS ") acid, ball milling (" BM "), calcination (" C "), sulfuric acid (" H SO ") and / or phosphoric acid (" H PO ") is compared with cement.The compressive strength of SCM from copper tailings is not obviously distinguished from cement.

[0055] Figure 6 The compressive strength of SCM prepared by asbestos tailings after 7 days and 28 days is shown. The compressive strength of mortar samples prepared with 20% of the SCM from asbestos tailings is shown. The SCM from asbestos tailings ("ASB") with hexafluorosilicic acid ("HFS"), ball milling ("BM"), calcination ("C"), and / or hydrochloric acid ("HCl") is compared with cement. The compressive strength of the SCM from asbestos tailings is not significantly different from cement.

[0056] Figure 7 The compressive strength of SCM prepared by laterite tailings after 7 days and 28 days is shown.The compressive strength of mortar samples prepared with 20% of the SCM from laterite tailings is shown.The SCM from laterite tailings (" LT") with hexafluorosilicic acid (" HFS ") and ball milling (" BM ") is compared with cement.The compressive strength of the SCM from laterite tailings is not obviously different from cement.

[0057] Figure 8 The compressive strength of SCM prepared from recycled concrete after 7 and 28 days is shown. The compressive strength of mortar samples prepared with 20% of SCM from recycled concrete is shown. SCM from concrete waste ("CW") with hexafluorosilicic acid ("HFS"), ball milled ("BM") and calcined ("C") is compared with cement. The compressive strength of SCM from recycled concrete is not significantly different from cement.

[0058] Fig. 9 and 10 Show the compressive strength of SCM prepared by nickel tailings after 7 days and 28 days of solidification in lime water.Show the compressive strength of mortar sample prepared with 20% SCM from nickel tailings.Show the SCM from nickel tailings with hexafluorosilicic acid (" HFS ") and ball milling (" BM ") and cement comparison.The compressive strength of SCM from nickel tailings is not obviously different from cement.

[0059] Fig.11 and 12 The compressive strength of SCM prepared by copper tailings after 7 days and 28 days of solidification in lime water is shown.The compressive strength of mortar samples prepared with 20% of the SCM from copper tailings is shown.The SCM from copper tailings with hexafluorosilicic acid (" HFS ") and ball milling (" BM ") is compared with cement.The compressive strength of the SCM from copper tailings is not obviously different from cement.

[0060] Fig.13 and 14 The compressive strength of SCM prepared by bottom ash, basalt, copper slag and zeolite after 7 days and 28 days of solidification in lime water is shown. The compressive strength of mortar samples prepared with 20% of the SCM from bottom ash, basalt, copper slag and zeolite is shown. The SCM from bottom ash, basalt, copper slag and zeolite with hexafluorosilicic acid (" HFS ") and ball milling (" BM ") is compared with cement. The compressive strength of the SCM from bottom ash, basalt, copper slag and zeolite is not obviously different from cement.

[0061] SCM can comprise minerals, and minerals include but are not limited to siliceous minerals, siliceous aluminum minerals, aluminum iron minerals, dolomite minerals, calcite minerals or magnesite minerals or their combinations. SCM can reduce the CO2 release caused by cement preparation. Tailings minerals can be activated by a combination of acid activation and grinding or low temperature calcination, acid activation and grinding. Tailings feed can come from various raw materials, including but not limited to: oil sands tailings that can be mainly clay, zinc and lead; copper tailings; base metal tailings; precious metal tailings; nickel laterite tailings; asbestos tailings; coal waste tailings; or their combinations. Activation can refer to the increased amorphous content of crystalline tailings feed caused by the structural disorder caused by a combination of acid treatment or acid treatment and calcination. The activated amorphous phases of these tailings minerals can participate in the pozzolanic reaction with the portlandite (Ca (OH) 2) from cement to form calcium silicate hydrate (CSH). Aluminum in tailings clay can also exist and undergo similar reactions to form aluminate calcium silicate hydrate (CASH). High crystallinity in tailings minerals may render them unsuitable for participating in pozzolanic reactions. However, amorphization of tailings minerals by acid activation or acid activation and calcination may render them suitable for participating in pozzolanic reactions and acting as cementitious materials.

[0062] The acid treatment of the tailings mineral comprising clay can cause protons to penetrate the mineral layer and attack the structural OH group. The dihydroxylation of gained is related to the continuous release of the central atom from the octahedron and is related to the removal of aluminum from the tetrahedral sheet. The gained solid product can comprise unchanged layers and amorphous silica. Acid activation can also increase the specific surface area of ​​the tailings mineral and / or the clay arranged in the tailings mineral, thereby increasing the reactivity of the tailings. The increase of specific surface area can be further realized by the ball milling of the tailings crossed by acid treatment and the clay arranged in the tailings. This volcanic ash formation method does not overlap with the method for forming SCM with high temperature calcined clay (higher than 700 ℃).

[0063] In the crystalline silicate structure, silicon atoms can be surrounded by oxygen atoms arranged in a tetrahedral manner (SiO4 4-). Crystalline silicate structures can be related to each other to allow for structural classification of silicate minerals, such as neosilicates, cyclosilicates, phyllosilicates, and reticular silicates. Other components of the silicate structure, including but not limited to OH groups and cations, can subsequently arrange with the silicate groups to produce an electrically neutral structure. The strongest bonds in the tetrahedron are Si and O ions. Metal cation-oxygen bonds can be weaker than silicon-oxygen bonds and can be more sensitive to acid attack. Therefore, mineral dissolution may begin with the release of alkali and alkaline earth cations from the crystal lattice into acidic solutions. The Al-O (mainly ionic) bonds in the tetrahedron may not be as strong as the Si-O bonds. Therefore, when dissolved in a medium and / or solution in which Al can migrate, the release of Al into the solution dominates relative to the release of Si. Si can accumulate in the solid phase in the form of amorphous compounds.

[0064] Dissolution of silicates in hydrofluoric acid can occur at rates several orders of magnitude higher than other mineral acids. The addition of hydrofluoric ("HF") acid can result in a significant increase in the rate of silicate dissolution. HF acid can be used in sandstone matrices, for example, by acidulating in oil and gas wells to dissolve siliceous minerals. HFS can be used for silicate dissolution and activation of crystalline silicate minerals present in tailings. HFS is a byproduct of the phosphate fertilizer industry and can be used in some applications such as water fluoridation and cryolite production. However, the large amounts of HFS produced each year are a major environmental pollutant if not properly handled. HFS can be used as a fluoride ion source for activation of minerals present in tailings, which can then be used as SCM.

[0065] The composition of the tailings as measured using X-ray fluorescence ("XRF") is given in Table 1, highlighting the major minerals present in the tailings.

[0066] Table 1: Composition of the tailings materials tested

[0067]

[0068] Metals can be extracted from a mineral stream (e.g., a mineral tailings and / or waste stream) by contacting the mineral stream with an acid to form an activated mineral stream and a leachate. The acid can extract the metals into the leachate, and the activated mineral stream can be dried and pulverized to form SCM.

[0069] Embodiments of the present invention provide a technology-based solution that overcomes the problems existing in the prior art in a technical manner, thereby satisfactorily solving the existing problems of concrete manufacturers, contractors and mining operators. Embodiments of the present invention achieve important benefits relative to the current state of the art, such as reduced greenhouse gas emissions, improved concrete strength and durability, and economical tailings disposal. Some of the unconventional steps of embodiments of the present invention include acid activation, calcination, and grinding of crystalline mineral tailings.

[0070] Industrial Applicability :

[0071] The present invention is further illustrated by the following non-limiting examples.

[0072] Examples 1 to 5 describe how Figure 3 The compressive strength of the prepared mortar samples with 20% SCM from oil sand tailings is shown in FIG.

[0073] Example 1

[0074] Use polyacrylamide (1100ppm) to flocculate the feed of cooked fine tailings (" MFT ") and use centrifuge dewatering. Subsequently, the MFT sludge is dried to obtain dry material. Subsequently, the dry material is mixed with 5%HFS acid solution to form slurry. The ratio of dry tailings to acid solution ratio is 3:1. After the tailings and acid are mixed, the slurry is left to react for a period of 12 hours at room temperature to form treated tailings sludge. After the reaction period is completed, the treated tailings sludge is dried and ball milled to prepare fine SCM material. Ball milling is carried out to ensure that finer material is obtained, which meets the fineness judgment standard listed in ASTMC618 for natural pozzolans. The SCM obtained from the oil sand tailings is subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix is ​​hardened to form SCM-concrete samples. The compressive strength of the test sample after 7 days and 28 days is then compared with the 100% cement control.

[0075] Example 2

[0076] Use polyacrylamide (1100ppm) to flocculate MTF feed and use centrifuge dewatering. MFT sludge is then dried to obtain dry material. Dried material is then mixed with 5% HFS acid solution to form slurry. The ratio of dry tailings to acid solution ratio is 3:1. After tailings are mixed with acid, slurry is left to react for 12 hours at room temperature to form treated tailings sludge. After the reaction time period is completed, treated tailings sludge is dried and calcined at 500°C for 60 minutes. Finally, acid activated and calcined tailings are ball milled to prepare fine SCM materials. Acid activated viscosity is further activated using a calciner at a temperature of 500°C, which is lower than commercially available calcined clays that are usually calcined at above 700°C. Acid activation of clay before calcination reduces the activation temperature for further dehydroxylation. SCM made from oil sand tailings is subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was allowed to harden to form SCM-concrete samples. The compressive strength of the samples was then tested after 7 and 28 days and compared with a 100% cement control.

[0077] Example 3

[0078] Use quaternary ammonium coagulant (comprising benzyl trimethyl ammonium chloride) (3000ppm) that MFT feed is condensed, and use centrifuge dehydration. MFT sludge is dried subsequently to obtain dry material. Dry material is mixed with 5%HFS acid solution subsequently to form slurry. The ratio of dry tailings and acid solution ratio is 3:1. After tailings and acid are mixed, slurry is left to stand at room temperature to react the time period of 12 hours to form treated tailings sludge. After the reaction time period is completed, the treated tailings sludge is dried and ball milled to prepare fine SCM material. Ball milling is carried out to ensure that finer material is obtained, which meets the fineness judgment standard listed in ASTM C618 for natural pozzolans. The SCM obtained by oil sand tailings is subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. Make the mortar mix harden to form SCM-concrete sample. The compressive strength of the test sample after 7 days and 28 days is compared with 100% cement control subsequently.

[0079] Example 4

[0080] First, the MFT feed is treated with sodium silicate to disperse the tailings and use flotation to remove asphalt. After flotation, the residual asphalt in the tailings is reduced by 70%. Remove asphalt to determine its impact on final SCM performance. Subsequently, polyacrylamide (1100ppm) is used for MFT flocculation, and centrifuge dewatering is used. Subsequently, the MFT sludge is dried to obtain dry material. Subsequently, the dry material is mixed with 5%HFS acid solution to form slurry. The ratio of dry tailings and acid solution ratio is 3:1. After the tailings and acid are mixed, the slurry is left to stand at room temperature to react the time period of 12 hours to form the treated tailings sludge. After the reaction time period is completed, the treated tailings sludge is dried, and ball milling is used to prepare fine SCM material. Ball milling is carried out to ensure that finer material is obtained, which meets the fineness judgment standard listed in the ASTM C618 for natural pozzolans. The SCM obtained by the oil sand tailings is subsequently used to replace 20% cement in the mortar mixture as outlined in ASTM C311. The mortar mix was allowed to harden to form SCM-concrete samples. The compressive strength of the samples was then tested after 7 and 28 days and compared with a 100% cement control.

[0081] Example 5

[0082] Use quaternary ammonium coagulant (comprising benzyl trimethyl ammonium chloride) (3000ppm) that MFT feed is condensed, and centrifuge is used for dehydration. Subsequently, MFT sludge is dried to obtain dry material. Subsequently, dry material is mixed with 7.5%HFS acid solution to form slurry. The ratio of dry tailings and acid solution ratio is 3:1. After tailings are mixed with acid, slurry is left to stand at room temperature to react for 12 hours to form treated tailings sludge. After the reaction time period is completed, the treated tailings sludge is dried and ball milled to prepare fine SCM material. Ball milling is carried out to ensure that finer material is obtained, which meets the fineness judgment standard listed in ASTM C618 for natural pozzolans. SCM obtained from oil sand tailings is subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. Make mortar mix harden to form SCM-concrete sample. Test sample compressive strength after 7 days and 28 days subsequently and compare with 100% cement control.

[0083] Examples 6 to 15 show that Figure 4 The compressive strength of the prepared mortar samples with 20% SCM from zinc tailings is shown in FIG.

[0084] Example 6

[0085] The dried zinc tailings were mixed with 5% HFS acid solution to form a slurry. The ratio of dried tailings to acid solution ratio was 3:1. After the tailings were mixed with acid, the slurry was left to react for a period of 12 hours at room temperature to form treated tailings sludge. After the reaction period was completed, the treated tailings sludge was dried and ball milled to prepare fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The ball milled tailings were then calcined at 500°C for 60 minutes. The SCM made from the zinc tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTMC311. The mortar mix was hardened to form SCM-concrete samples. The compressive strength of the samples was then tested for 7 days and 28 days and compared with a 100% cement control.

[0086] Example 7

[0087] First, the dried zinc tailings were ball milled to prepare fine materials that met the fineness judgment standards listed in ASTM C618 for natural pozzolans and to increase the surface area before calcination and subsequent acid activation. The ball milled samples were then calcined at 500°C for 60 minutes. After calcination, the tailings were mixed with a 5% HFS acid solution to form a slurry. The ratio of the dried tailings to the acid solution ratio was 3:1. After the tailings and acid were mixed, the slurry was left to react for a period of 12 hours at room temperature to form a treated tailing sludge. After the reaction period was complete, the treated tailing sludge was dried and powdered to break up any aggregates. The SCM made from the zinc tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form an SCM-concrete sample. The compressive strength of the sample was then tested after 7 and 28 days and compared with a 100% cement control.

[0088] Example 8

[0089] The dried zinc tailings were calcined at 500°C for 60 minutes. After calcination, the tailings were mixed with 5% HFS acid solution to form a slurry. The ratio of dried tailings to acid solution ratio was 3:1. After the tailings were mixed with acid, the slurry was left to react for a period of 12 hours at room temperature to form treated tailings sludge. After the reaction period was completed, the treated tailings sludge was dried and ball milled to prepare fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The SCM obtained from the zinc tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTMC311. The mortar mix was hardened to form SCM-concrete samples. The compressive strength of the samples was subsequently tested for 7 days and 28 days and compared with a 100% cement control.

[0090] Example 9

[0091] The dried zinc tailings were mixed with 7.5% HFS acid solution to form a slurry. The ratio of dried tailings to acid solution ratio was 3:1. After the tailings and acid were mixed, the slurry was left to react for one hour at 80°C to form treated tailings sludge. After the reaction time period was completed, the treated tailings sludge was dried and ball milled to prepare fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The ball milled tailings were then calcined at 500°C for 60 minutes. The SCM made from the zinc tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTMC311. The mortar mix was hardened to form SCM-concrete samples. The compressive strength of the samples was then tested for 7 days and 28 days and compared with a 100% cement control.

[0092] Example 10

[0093] The dried zinc tailings were mixed with 5% HFS acid solution to form a slurry. The ratio of dried tailings to acid solution ratio was 3:1. After the tailings and acid were mixed, the slurry was left to react for one hour at room temperature to form treated tailings sludge. After the reaction time period was completed, the treated tailings sludge was dried and ball milled to prepare fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The ball milled tailings were then calcined at 500°C for 60 minutes. The SCM made from the zinc tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTMC311. The mortar mix was hardened to form SCM-concrete samples. The compressive strength of the samples was then tested for 7 days and 28 days and compared with a 100% cement control.

[0094] Embodiment 11

[0095] First, the dried zinc tailings were ball milled to prepare fine materials that met the fineness judgment standards listed in ASTM C618 for natural pozzolans and to increase the surface area before calcination and subsequent acid activation. The ball milled material was then calcined at 500°C for 60 minutes. After calcination, the tailings were mixed with a 5% HFS acid solution to form a slurry. The ratio of the dried tailings to the acid solution ratio was 3:1. After the tailings and acid were mixed, the slurry was left to react for a period of one hour at room temperature to form a treated tailing sludge. After the reaction period was completed, the treated tailing sludge was dried and replaced with ball milling to break the aggregates. The SCM made from the zinc tailings was then used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form an SCM-concrete sample. The compressive strength of the sample was then tested after 7 and 28 days and compared with a 100% cement control.

[0096] Example 12

[0097] Dry zinc tailings are mixed with 5%HFS acid solution. The ratio of dry tailings to acid solution ratio is 3:1 to form slurry. After tailings are mixed with acid, slurry is left to stand at room temperature to react for 12 hours to form treated tailings sludge. After the reaction time period is completed, the treated tailings sludge is dried and ball milled to prepare fine SCM material. Ball milling is carried out to ensure that finer material is obtained, which meets the fineness judgment standard listed in ASTM C618 for natural pozzolans. The SCM obtained from zinc tailings is subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix is ​​hardened to form SCM-concrete samples. The compressive strength of the test sample after 7 days and 28 days is then compared with 100% cement control.

[0098] Example 13

[0099] The dried zinc tailings were ball milled to prepare fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness criteria listed in ASTM C618 for natural pozzolans. The ball milled tailings were then calcined at 500°C for 60 minutes. The SCM made from the zinc tailings was then used to replace 20% of the cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form SCM-concrete samples. The compressive strength of the samples was then tested after 7 and 28 days and compared with a 100% cement control.

[0100] Embodiment 14

[0101] The dried zinc tailings were mixed with 5% aqua regia solution replacing HFS acid to form a slurry. The ratio of dried tailings to acid solution ratio was 3:1. After the tailings were mixed with acid, the slurry was left to react for a period of 12 hours at room temperature to form treated tailings sludge. After the reaction period was complete, the treated tailings sludge was dried and ball milled to prepare fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The ball milled tailings were then calcined at 500°C for 60 minutes. The SCM made from the zinc tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form SCM-concrete samples. The compressive strength of the samples was then tested after 7 and 28 days and compared with a 100% cement control.

[0102] Embodiment 15

[0103] The dried zinc tailings were mixed with a mixture of 5% HFS acid solution and 1% H2SO4 in a mass ratio of 3:1 to form a slurry. The ratio of the dried tailings to the HFS and H2SO4 acid solution ratio was 3:1. After the tailings were mixed with the acid, the slurry was left to react for a period of 12 hours at room temperature to form a treated tailings sludge. After the reaction period was completed, the treated tailings sludge was dried and ball milled to prepare a fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The ball milled tailings were then calcined at 500°C for 60 minutes. The SCM obtained from the zinc tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form an SCM-concrete sample. The compressive strength of the sample was then tested for 7 days and 28 days and compared with a 100% cement control.

[0104] Examples 19 to 23 describe how Figure 5 The compressive strength of the prepared mortar samples with 20% SCM from copper tailings is shown in FIG.

[0105] Embodiment 19

[0106] First, the dried copper tailings were ball milled to prepare fine materials that met the fineness judgment standards listed in ASTM C618 for natural pozzolans and to increase the surface area before calcination and subsequent acid activation. The ball milled material was then calcined at 500°C for 60 minutes. After calcination, the tailings were mixed with a 5% HFS acid solution to form a slurry. The ratio of the dried tailings to the acid solution ratio was 3:1. After the tailings were mixed with the acid, the slurry was left to react for a period of 12 hours at room temperature to form a treated tailing sludge. After the reaction period was complete, the treated tailing sludge was dried and powdered to break any aggregates. The SCM made from the copper tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form an SCM-concrete sample. The compressive strength of the sample was then tested for 7 days and 28 days and compared with a 100% cement control.

[0107] Embodiment 20

[0108] The dried copper tailings were calcined at 500°C for 60 minutes. After calcination, the tailings were mixed with 5% HFS acid solution to form a slurry. The ratio of dried tailings to acid solution ratio was 3:1. After the tailings were mixed with acid, the slurry was left to react for a period of 12 hours at room temperature to form treated tailings sludge. After the reaction period was completed, the treated tailings sludge was dried and ball milled to prepare fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The SCM obtained from the copper tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form SCM-concrete samples. The compressive strength of the sample was subsequently tested for 7 days and 28 days and compared with a 100% cement control.

[0109] Embodiment 21

[0110] First, the dried copper tailings were ball milled to prepare fine materials that met the fineness judgment standards listed in ASTM C618 for natural pozzolans and to increase the surface area before calcination and subsequent acid activation. The ball milled material was then calcined at 500°C for 60 minutes. After calcination, the tailings were mixed with a 7.5% HFS acid solution to form a slurry. The ratio of the dried tailings to the acid solution ratio was 3:1. After the tailings were mixed with the acid, the slurry was left to react for a period of 12 hours at room temperature to form a treated tailing sludge. After the reaction period was completed, the treated tailing sludge was dried and replaced with ball milling to break up any aggregates. The SCM made from the copper tailings was then used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form an SCM-concrete sample. The compressive strength of the sample was then tested after 7 and 28 days and compared with a 100% cement control.

[0111] Embodiment 22

[0112] The dried copper tailings were mixed with a mixture of 5% HFS acid solution and 1% H3PO4 in a mass ratio of 3:1 to form a slurry. The ratio of dried tailings to HFS and H3PO4 acid solution ratio was 3:1. After the tailings were mixed with acid, the slurry was left to react for a period of 12 hours at room temperature to form treated tailings sludge. After the reaction period was completed, the treated tailings sludge was dried and ball milled to prepare fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The ball milled tailings were subsequently calcined at 500°C for 60 minutes. The SCM obtained from the copper tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form SCM-concrete samples. The compressive strength of the sample was subsequently tested for 7 days and 28 days and compared with a 100% cement control.

[0113] Embodiment 23

[0114] The dried copper tailings were mixed with a mixture of 5% HFS acid solution and 1% H2SO4 in a mass ratio of 3:1 to form a slurry. The ratio of dried tailings to HFS and H2SO4 acid solution ratio was 3:1. After the tailings were mixed with acid, the slurry was left to react for a period of 12 hours at room temperature to form treated tailings sludge. After the reaction period was completed, the treated tailings sludge was dried and ball milled to prepare fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The ball milled tailings were subsequently calcined at 500°C for 60 minutes. The SCM obtained from the copper tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form SCM-concrete samples. The compressive strength of the sample was then tested for 7 days and 28 days and compared with a 100% cement control.

[0115] Examples 24 to 28 show that Figure 6 Compressive strength of prepared mortar samples with 20% SCM from asbestos tailings shown in .

[0116] Embodiment 24

[0117] The dried asbestos tailings were calcined at 500°C for 60 minutes. After calcination, the tailings were ball milled to further destroy asbestos fibers and prepare finer materials. After ball milling, the tailings were mixed with 5% HFS acid solution to form a slurry. The ratio of dried tailings to acid solution ratio was 3:1. After the tailings were mixed with acid, the slurry was left to react for a period of 12 hours at room temperature to form treated tailings sludge. After the reaction period was completed, the treated tailings sludge was dried and ball milled to break the aggregates and prepare SCM materials. The SCM made from the asbestos tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form SCM-concrete samples. The compressive strength of the sample was subsequently tested for 7 days and 28 days and compared with a 100% cement control.

[0118] Embodiment 25

[0119] The mixture of dry asbestos tailings and 5% HFS acid solution is mixed to form a slurry. The ratio of dry tailings to HFS solution is 3:1. After the tailings are mixed with acid, the slurry is left to react for a period of 12 hours at room temperature to form treated tailings sludge. After the reaction period is completed, the treated tailings sludge is dried and calcined at 500°C for 60 minutes. After acid treatment and calcination, the tailings are ball milled to completely destroy the fibers and prepare fine SCM materials. The SCM made from the asbestos tailings is subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix is ​​hardened to form SCM-concrete samples. The compressive strength of the sample is subsequently tested for 7 days and 28 days and compared with a 100% cement control.

[0120] Embodiment 26

[0121] Dry asbestos tailings are mixed with a mixture of 5% HFS acid solution and 1% hydrochloric acid (" HCL ") with a mass ratio of 3: 1 to form a slurry. The ratio of dry tailings to HFS and HCL acid solution ratio is 3: 1. After the tailings are mixed with acid, the slurry is left to react for a period of 12 hours at room temperature to form treated tailings sludge. After the reaction period is completed, the treated tailings sludge is dried and calcined at 500 ° C for 60 minutes. After acid treatment and calcination, the tailings are ball milled to completely destroy the fiber and prepare fine SCM materials. The SCM made from the asbestos tailings is subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix is ​​hardened to form SCM-concrete samples. The compressive strength of the sample is then tested after 7 days and 28 days and compared with 100% cement controls.

[0122] Example 27 shows that Figure 7 The compressive strength of the prepared mortar samples with 20% of SCM from laterite tailings shown in FIG.

[0123] Embodiment 27

[0124] The mixture of dry laterite tailings and 5%HFS acid solution is mixed to form slurry. The ratio of dry tailings to HFS solution is 3:1. After tailings are mixed with acid, slurry is left to react for 12 hours at room temperature to form treated tailings sludge. After acid treatment, treated tailings sludge is ball milled to prepare fine SCM material, which meets the fineness judgment standard according to ASTM C618. The SCM made from laterite tailings is subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix is ​​hardened to form SCM-concrete samples. The compressive strength of the test sample after 7 days and 28 days is then compared with 100% cement control.

[0125] Example 28 shows that Figure 8 Compressive strength of the prepared mortar samples with 20% of SCM from concrete waste shown in .

[0126] Embodiment 28

[0127] First, the concrete waste is broken to remove aggregates and separate finer cementitious materials. The finer materials are then mixed with a mixture of 5% HFS acid solution to form a slurry. The ratio of recycled concrete waste to HFS solution is 3:1. After mixing the concrete waste with acid, the slurry is left to react at room temperature for a period of 12 hours to form concrete waste. After acid treatment, the concrete waste is ball milled to prepare a fine SCM material that meets the fineness judgment standard according to ASTM C618. After ball milling, the concrete waste is calcined at 500°C for further activation. The SCM made from the concrete waste is then used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix is ​​hardened to form an SCM-concrete sample. The compressive strength of the sample is then tested after 7 days and 28 days and compared with a 100% cement control.

[0128] Examples 29 to 35 describe the SCM preparation and metal extraction process from tailings using the acid activation process alone.

[0129] Examples 29 and 30 describe the treatment of nickel tailings with HFS to extract nickel and other components in the leachate. The following activation process does not involve any calcination for further activation of the tailings. The addition of higher amounts of HFS can activate the mineral stream alone.

[0130] Embodiment 29

[0131] The mixture of dried nickel tailings-1 and 1M HFS acid solution is mixed with a mass ratio of 1:1 to form a slurry. The ratio of dried tailings to 1M HFS solution ratio is 1:1. After the tailings are mixed with acid, the slurry is stirred at 60°C for 1 hour. After the reaction period is completed, the treated tailings slurry is filtered to extract the leachate and the sludge is neutralized with lime. The neutralized tailings sludge is dried and ball-milled to prepare fine SCM materials. Ball milling is performed to ensure that a finer material is obtained, which meets the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The SCM made from the nickel tailings is subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix is ​​hardened to form an SCM-concrete sample. The compressive strength of the sample after curing in lime water for 7 days and 28 days is then tested and compared with a 100% cement control cured in lime water. The amount of nickel extracted in the leachate was 1972 ppm as measured by inductively coupled plasma mass spectrometry ("CP-MS").

[0132] Embodiment 30

[0133] Another set of dried nickel tailings-2 with slightly different mineralogy was mixed with a mixture of 1M HFS acid solution in a mass ratio of 1:1 to form a slurry. The ratio of dried tailings to 1M HFS solution ratio was 1:1. After the tailings were mixed with acid, the slurry was stirred at 60°C for 1 hour. After the reaction period was completed, the treated tailings slurry was filtered to extract the leachate and the sludge was neutralized with lime. The neutralized tailings sludge was dried and ball milled to prepare fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The SCM made from the nickel tailings was subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form an SCM-concrete sample. The compressive strength of the sample was then tested after curing in lime water for 7 days and 28 days and compared with a 100% cement control cured in lime water. The amount of nickel extracted in the leachate was 700 ppm as measured by ("ICP-MS").

[0134] Example 31 describes the treatment of copper tailings with HFS to extract copper and other components in the leachate. The following activation process does not involve any calcination for further activation of the tailings. The addition of higher amounts of HFS can activate the mineral stream alone.

[0135] Embodiment 31

[0136] The mixture of dried copper tailings and 1M HFS acid solution is mixed with a mass ratio of 1:1 to form a slurry. The ratio of dried tailings to 1M HFS solution ratio is 1:1. After the tailings and acid are mixed, the slurry is stirred at 60°C for 1 hour. After the reaction period is completed, the treated tailings slurry is filtered to extract the leachate and the sludge is neutralized with lime. The neutralized tailings sludge is dried and ball milled to prepare fine SCM materials. Ball milling is performed to ensure that a finer material is obtained, which meets the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The SCM made from the copper tailings is subsequently used to replace 20% cement in the mortar mix as outlined in ASTM C311. The mortar mix is ​​hardened to form an SCM-concrete sample. The compressive strength of the sample after curing in lime water for 7 days and 28 days is then tested and compared with a 100% cement control cured in lime water. The amount of nickel extracted in the leachate was 10996 ppm as measured by ICP-MS.

[0137] Example 32 describes the use of HFS to increase the reactivity of mineral streams with relatively low pozzolanic activity (such as bottom ash, basalt, copper slag and zeolites). The following activation process does not involve any calcination.

[0138] Embodiment 32

[0139] A mixture of dried bottom ash and 0.5M HFS acid solution was mixed in a mass ratio of 1:1 to form a slurry. The ratio of bottom ash to 0.5M HFS solution ratio was 1:1. After mixing the bottom ash with the acid, the slurry was stirred at 60°C for 1 hour. After the reaction period was completed, the treated bottom ash slurry was filtered and neutralized with lime. The neutralized bottom ash sludge was dried and ball milled to prepare a fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The SCM prepared from the bottom ash was then used to replace 20% of the cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form an SCM-concrete sample. The compressive strength of the sample was then tested after curing for 7 and 28 days in lime water and compared with a 100% cement control cured in lime water.

[0140] Embodiment 33

[0141] A mixture of dried basalt and 0.5M HFS acid solution was mixed in a mass ratio of 1:1 to form a slurry. The ratio of basalt to 0.5M HFS solution ratio was 1:1. After mixing the basalt with the acid, the slurry was stirred at 60°C for 1 hour. After the reaction period was completed, the treated basalt slurry was filtered and neutralized with lime. The neutralized basalt sludge was dried and ball milled to prepare a fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The SCM made from basalt was then used to replace 20% of the cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form an SCM-concrete sample. The compressive strength of the sample was then tested after curing for 7 and 28 days in lime water and compared with a 100% cement control cured in lime water.

[0142] Embodiment 34

[0143] A mixture of dried copper slag and 1M HFS acid solution was mixed in a mass ratio of 1:1 to form a slurry. The ratio of copper slag to 1M HFS solution ratio was 1:1. After the copper slag was mixed with the acid, the slurry was stirred at 60°C for 1 hour. After the reaction period was completed, the treated copper slag slurry was filtered and neutralized with lime. The neutralized copper slag sludge was dried and ball milled to prepare a fine SCM material. Ball milling was performed to ensure that a finer material was obtained, which met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The SCM made from copper slag was then used to replace 20% of the cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form an SCM-concrete sample. The compressive strength of the sample was then tested after curing in lime water for 7 days and 28 days and compared with a 100% cement control cured in lime water.

[0144] Embodiment 35

[0145] A mixture of dried zeolite and 1M HFS acid solution was mixed in a mass ratio of 1:1 to form a slurry. The ratio of zeolite to 1M HFS solution ratio was 1:1. After mixing the zeolite with the acid, the slurry was stirred at 60°C for 1 hour. After the reaction period was completed, the treated zeolite slurry was filtered and neutralized with lime. The neutralized zeolite sludge was dried and ball milled to prepare a fine SCM material. Ball milling was performed to ensure that a finer material was obtained that met the fineness judgment criteria listed in ASTM C618 for natural pozzolans. The SCM made from zeolite was then used to replace 20% of the cement in the mortar mix as outlined in ASTM C311. The mortar mix was hardened to form an SCM-concrete sample. The compressive strength of the sample was then tested after curing in lime water for 7 days and 28 days and compared with a 100% cement control cured in lime water.

[0146] The preceding examples can be repeated with similar success by substituting the generically or specifically described reactants and / or operating conditions of the present invention for those used in the preceding examples.

[0147] Note that in this specification and claims, "about" or "approximately" means within twenty percent (20%) of the referenced quantity. Unless the context clearly indicates otherwise, the terms "a," "an," "the," and "said" mean "one or more."

[0148] Embodiments of the present invention may include every combination of features disclosed independently of one another in this article. Although the present invention has been described in detail with specific reference to disclosed embodiments, other embodiments can achieve the same result. Variations and changes of the present invention will be obvious to those skilled in the art, and are intended to cover all these changes and equivalents. The complete disclosures of all references, applications, patents and publications cited above are incorporated herein by reference. Unless specifically illustrated as "essential" above, none of the various components or their mutual relationships are essential for the operation of the present invention. On the contrary, the desired result can be achieved by replacing the various components and / or reconstructing their relationship.

Claims

1. A method for preparing an auxiliary gelling material, the method comprising: contacting the mineral stream with an acid to form an activated mineral stream; reducing the moisture content of the mineral stream; as well as The mineral stream is comminuted to form a supplementary cementitious material.

2. The process of claim 1, wherein the mineral stream comprises tailings.

3. The method of claim 1, wherein the mineral stream is contacted with the acid for about 1 to about 24 hours.

4. The method of claim 1, wherein reducing the moisture content comprises drying.

5. The method of claim 1, wherein comminuting comprises ball milling.

6. The method of claim 1, wherein the acid comprises hexafluorosilicic acid.

7. The method of claim 1, wherein the acid comprises sulfuric acid.

8. The method of claim 1, wherein the acid comprises phosphoric acid.

9. The method of claim 1, further comprising calcining the activated mineral stream.

10. The method of claim 9, wherein the activated mineral stream is calcined at a temperature of about 500°C to about 700°C.

11. The method of claim 1 , wherein the mineral stream comprises asbestos tailings.

12. The method of claim 1, wherein the mineral stream comprises laterite tailings.

13. The method of claim 1, wherein the mineral stream comprises oil sands tailings.

14. A method of extracting a metal from a mineral stream, the method comprising: contacting the mineral stream with an acid to form an activated mineral stream; filtering the activated mineral stream to extract a leachate comprising the metal; as well as The acid is neutralized.

15. The method of claim 14, wherein the acid comprises hexafluorosilicic acid.

16. The method of claim 14, wherein the mineral stream comprises tailings.

17. The method of claim 14, wherein the mineral stream comprises sludge.

18. The method of claim 14, wherein the mineral stream comprises slag.

19. The method of claim 14, wherein neutralizing the acid comprises contacting the activated tailings with a caustic.

20. The method of claim 19, wherein the caustic comprises lime.